Apply the information-motivation-behavioral model to explore the relationship between oral health literacy and oral health behaviors among community-dwelling older adults - Yiqing Liang; Songmei Cao; Huiling Xu; Shuhua Wang; Man Feng; Jingjing Wang; Yimeng Fan (BMC, 2024)
Abstract Objective Oral health is a critical area in healthy aging. Oral health literacy (OHL) plays an important role in improving oral health behaviors and oral health status. However, few studies have investigated OHL among community-dwelling older adults and the influential mechanism of OHL on oral health behaviors has not been clarified. The aim of this study is to explore the interaction pathways through which OHL influences oral health behaviors among community-dwelling older adults. Methods This is a cross-sectional study. 429 community-dwelling older adults were recruited by a convenience sampling method from the activity service center in Zhenjiang, Southern China. The data were collected between September and November 2021 using the Oral Health Literacy Adult Questionnaire (OHL-AQ) and other sophisticated scale assessments. A theoretical model based on the information-motivation-behavioral skills model (IMB model) and previous research was developed and then validated using a structural equation model with AMOS v24.0. Results The proposed model revealed a good fit to the data (χ2/df = 3.349, goodness of fit index = 0.957, adjusted goodness of fit index = 0.921, root mean squared error of approximation = 0.074, comparative fit index = 0.955, normed fit index = 0.938). Oral health information (β = 0.23) and motivation (β = 0.56) positively affected OHL. OHL (β = 0.20) and motivation (β = 0.25) positively affected self-efficacy; self-efficacy (β = 0.98) had a direct effect on oral health behavior. OHL had an indirect effect on oral health behaviors through self-efficacy (β = 0.19). Motivation can both directly influence oral health behavior (β = 0.18) and indirectly influence oral health behavior through OHL and self-efficacy(β = 0.35). Conclusions The study findings make a valuable contribution to the influential mechanism of OHL on oral health behaviors. OHL improved oral health behaviors through self-efficacy among community-dwelling older adults. Oral health information directly affected OHL. Motivation directly affected oral health behaviors as well as influence oral health behaviors by changing OHL.